Nanozymes Induced Air Purification- A State of the Art Review - Sarkar, Abhijeet; Saha, Ashmita; Bhattacharjee, Bhaskar; Sahoo, Bishnupada; Bakshi, Rounak; Podder, Soumik (Recent Research Reviews Journal, 2023)
Air decontamination is always a prime concern to society as the air to be inhaled should be free of contaminants so that living beings can get ample amount of energy to wheel their lives. Rapid urbanization causes drastic contamination in air that can create several life-threatening disorders. In this scenario, ultrahigh detection along with quick estimation of air pollutants has become an urgent need to the society. Nanotechnology enabled enzyme mimicking materials known as nanozymes, demonstrates elevated purification efficiency, sterilizability and low wind resistance. These materials when used in air-filter can work as a soldier to combat with air pollution. Incorporation of latest technology viz. Internet of Things (IoT), cloud computing, etc., brings a new flavor in air refinement. In this present work, several nanozymes are surveyed with high efficiency in air filtration. Single atom nanozymes have established themselves as proficient candidates in air decontamination. The implication in air refinement is attributed to the birth of pro-active superoxide ions and successive formaldehyde oxidation. Corona virus and microbes afflicted air may be purified by the redox commotion of nanozymes. Fiber centric air filter provides enhanced filtration efficiency in real time monitoring process with the aid of IoT conjugation. The present review aids in understanding the mechanisms and potentiality of nanozymes as air purifiers, and also optimizes the design of air purifier.